The kings’ position in the Atlantic slave trade: Portugal, Dahomey and Ardra/Hogbonu, 1810-1812 - de Carvalho Soares, Mariza (Revista Crítica Histórica, 2022)
The article addresses the connection between two West African kingdoms (Ardra/Hogbonu and Dahomey) and Portugal, from 1810 to 1812. In 1810 Portugal and Great Britain signed the Strangford Treaty (in Brazil known as Treaty of Alliance and Friendship) that committed Portugal with the progressive extinction with the trade of human beings from Africa to the Americas. The research was based in a wide range of documents involving Dahomian and Brazilian History in order to highlight the role of African rulers in the debate about the end of the Atlantic slave trade.